k = Kris' age 5 years ago

(2/3)k = Ben's age 5 years ago

k + 15 = Kris' age 10 years from now ← added 15 onto age 5 years ago

(2/3)k + 15 = Ben's age 10 years from now ← added 15 onto age 5 years ago

(2/3)k + 15 = (5/6)(k + 15) ← ten years from now, Ben will be 5/6 as old as Kris

4k + 90 = 5(k + 15) ← multiplied entire equation by 6, eliminating fractions

4k + 90 = 5k + 75 ← distributed

k = 15 ← subtracted 4k and 75

(2/3)k = 10 ← substituted 15 for k

Kris is 15

Ben is 10

- Proof

**
**